2017
DOI: 10.5194/hess-2017-610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skilful seasonal forecasts of streamflow over Europe?

Abstract: Abstract. This paper presents a Europe-wide analysis of the skill of the newly operational EFAS (European FloodAwareness System) seasonal streamflow forecasts, benchmarked against the Ensemble Streamflow Prediction (ESP) forecasting approach. The results suggest that, on average, the System 4 seasonal climate forecasts improve the streamflow predictability over historical meteorological observations for the first month of lead time only. However, the predictability 15 varies in space and time and is greater in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 37 publications
0
30
1
Order By: Relevance
“…We develop our forecasting framework in the Midwest because the drivers of streamflow variability are relatively well understood in the region (e.g., Slater & Villarini, 2017). The climate exhibits average annual temperatures ranging from less than 3°C in northern Minnesota to over 15°C in southeastern Missouri and average annual precipitation from~500 mm to~1200 mm in the same areas (Andresen et al, 2012). The Midwest has also witnessed a notable increase in precipitation (Alter et al, 2018) and flooding (Mallakpour & Villarini, 2015) in recent decades.…”
Section: Data Sets Of Observed Streamflow Precipitation Temperaturementioning
confidence: 99%
“…We develop our forecasting framework in the Midwest because the drivers of streamflow variability are relatively well understood in the region (e.g., Slater & Villarini, 2017). The climate exhibits average annual temperatures ranging from less than 3°C in northern Minnesota to over 15°C in southeastern Missouri and average annual precipitation from~500 mm to~1200 mm in the same areas (Andresen et al, 2012). The Midwest has also witnessed a notable increase in precipitation (Alter et al, 2018) and flooding (Mallakpour & Villarini, 2015) in recent decades.…”
Section: Data Sets Of Observed Streamflow Precipitation Temperaturementioning
confidence: 99%
“…The most favorable years could be chosen from snow measurements during winter and seasonal forecasts of the flow peak during spring. Monthly seasonal forecasts of spring flow show skills in the region (Arnal et al, 2017;Foster et al, 2017), although low, and the efficiency of the artificially induced floods will increase with help of natural high flow also from unregulated areas contributing to flooding of the floodplains.…”
Section: Discussionmentioning
confidence: 99%
“…They found that S4 performs better than both ESPs at longer lead times. Contrarily, Arnal et al (2018), who studied LISFL-OOD seasonal streamflow forecasts over Europe with a spatial resolution of 0.7°, found that, on average, ESPs perform better than S4 for longer lead times, though this differs per season. It remains to be explored if this would also be the case for high resolution data in Catalonia.…”
Section: The Use Of Lisflood and Ecmwf Seas4mentioning
confidence: 99%
“…In probabilistic hydrological forecasts, a hydrological model is forced by probabilistic weather forecasts. On the other hand, ESP indicates that a hydrological model is initialized with current hydrological conditions, that subsequently is driven with different samples of historical meteorological data (Wood and Lettenmaier, 2008;Shukla and Lettenmaier, 2011;Staudinger and Seibert, 2014;Arnal et al, 2018;Monhart et al, 2019). In this study, we use probabilistic hydrological forecasts, which are, from now on, referred to as "hydrological drought forecasts".…”
Section: Introductionmentioning
confidence: 99%